Formulasi Bubur Instan Ubi Jalar Kuning (Ipomea batatas L.) Kaya Serat dengan Kombinasi Biji Kecipir (Psophocarpus tetra gonolobus) sebagai Sumber Protein - Jennifer Capriati Saragih; Reza Widyasaputra; Ida Bagus Banyuro Partha (Program Studi Teknologi Hasil Pertanian, 2024)
Instant porridge is a product designed to provide convenience and ease of serving. This study aims to determine the characteristics of instant porridge of yellow sweet potato and kecipir seeds as well as the organoleptic most favored by panelists. The experimental design used was a Complete Block Design (RBL) with 2 factors. Factor P was the ratio of yellow sweet potato and kecipir seeds P1 (80%:20%), P2 (70%:30%), P3 (60%:40%)Factor S is the difference in drying temperature, namely S1 (1050C), S2 (1150C), S3 (1250C). In the analysis of water content, the best sample in P3S3 is 3.57%, analysis of ash content of the best sample in P3S3 is 3.55%, analysis of fat content of the best sample in P3S3 is 8.50%, analysis of protein content of the best sample in P3S1 is 14.60%, analysis of carbohydrate content of the best sample is 73.62%, analysis of crude fiber content of the best sample in P1S3 is 4.58. In the rehydration power analysis, the best sample in P1S1 is 3.73 mL/g, the best rehydration time analysis in P1S3 is 9.89 seconds.